KESETARAAN GENDER DALAM PANDANGAN ASGHAR ALI ENGINEER: INTERPRETASI ANTARA TEKS KEAGAMAAN DAN KONTEKS SOSIAL - Farida Nur Afifah; Ainun Hakiemah (Mafatih, 2022)
Gender issue have given birth to different roles, function, responsibilities and rights, as well as activities of men and woman in social society. This mistake have implications for discriminatory attitudes in treating access, participation and social control. In the view of Islam it has never been a matter of gender, because it’s already explained in the Quran. Islam have provided justice between men and woman proportionally, women have a comprehensive and aqual role as men as servants of Allah and carry out the mandate. It’s needs a solution to reduce the existence of gender disparities in society. This paper will discuss about Asghar Ali Engineer’s view of gender. This paper is analyzed by looking for a variety of related literature. The result is that the Engineer offer two methods, contextual normative and transcedental. Namely reinterpreting the text of the Quran abaout gender which is the contextualized with the local socio-culture, because the law has a flexibel nature to follow the changing times.